Bài 1: tìm X, biết: a) (x +2)2 + (x-3)2 = 2x (x+7) b) (x+3).(x2 – 3x +9) = x(x2 +4) -1 c) (x+1)3 +( x-1)3 =x3 d) (2x +1)2 =16 giúp tui

Bài 1: tìm X, biết:
a) (x +2)2 + (x-3)2 = 2x (x+7)
b) (x+3).(x2 – 3x +9) = x(x2 +4) -1
c) (x+1)3 +( x-1)3 =x3
d) (2x +1)2 =16
giúp tui

0 bình luận về “Bài 1: tìm X, biết: a) (x +2)2 + (x-3)2 = 2x (x+7) b) (x+3).(x2 – 3x +9) = x(x2 +4) -1 c) (x+1)3 +( x-1)3 =x3 d) (2x +1)2 =16 giúp tui”

  1. Đáp án:a, (x+2)2+(x-3)2=2x(x+7)

    x.2+2.2+x.2+(-3).2-2x=8

    2x+4+2x-6-2x=8

    (2x+2x)+(4-6)=8

    4x-2=8

    4x=8+2

    4x=10

       X=10:4

        X=5/2

     Mk làm bn câu a đây r nhé chúc bn làm tốt ❤️❤️

    Giải thích các bước giải:

     

    Bình luận

Viết một bình luận